Dual orexin receptor antagonists for the treatment of insomnia: systematic review and network meta-analysis - Rocha, Rebeka Bustamante; Bomtempo, Fernanda Ferreira; Nager, Gabriela Borges; Cenci, Giulia Isadora; Telles, João Paulo Mota (Arquivos de Neuro-Psiquiatria, 2023)
Background Several randomized clinical trials (RCTs) have shown that dual orexin receptor antagonists (DORAs) are effective in the treatment of chronic insomnia. However, the superiority of one particular DORA over the others remains unclear.Objective To perform a network meta-analysis to evaluate the efficacy of different DORAs in patients with chronic insomnia.Methods The Medline, Embase, and Cochrane Central databases were searched for RCTs that compared DORA with placebo in patients ≥ 18 years of age with a diagnosis of insomnia disorder. We pooled outcomes for wake time after sleep onset (WASO), latency to persistent sleep (LPS), total sleep time (TST), and adverse events (AEs).Results We included 10 RCTs with 7,806 patients, 4,849 of whom received DORAs as the intervention. Overall, we found that DORAs were associated with the improvement of all analyzed efficacy outcomes. Concerning TST, an apparent dose-dependent pattern was noticed, with higher doses relating to a longer TST. Lemborexant 10mg provided the largest reduction in WASO (at month 1) in minutes (standardized mean difference [SMD] = -25.40; 95% confidence interval [95%CI] = -40.02–-10.78), followed by suvorexant 20/15mg (SMD = -25.29; 95%CI = -36.42–-14.15), which also appeared to provide the largest decrease in long-term WASO (SMD = -23.70; 95%CI = -35.89–-11.51). The most frequent AEs were somnolence, nasopharyngitis, and headache, with rates of up to 14.8%.Conclusion Our results suggest that DORAs are associated with greater efficacy when compared with placebo in the treatment of insomnia, a complex 24-hour sleep disorder. Additionally, dosing might play an important role in the management of chronic insomnia.
Keywords: Orexin Receptor Antagonists; Sleep Initiation and Maintenance Disorders